PENGARUH PENGAWASAN DAN DISIPLIN TERHADAP TINGKAT KINERJA KARYAWAN (Study Kasus Pada PT. Putra Jaya Sentosa Pekanbaru) - Firda Nova Manullang; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine the effect of supervision and discipline employee performance level in Putra Jaya Sentosa Pekanbaru Company. Supervision as an independent variable (X1), The discipline as an intervening variable (X2), and the employee performance level as the dependent variable (Y). This study took of respondents as many as 70 people.The data obtained through questionnaires and then further processed to be tested through statistical analysis such as multiple linear regression analysis, testing instruments and testing hypotheses of regression coefficient by using SPSS version 17.The results showed that the influence of supervision and discipline of the performance level that is known to control t (1,639)<t table (1,996)and sig (1,106)>0,05. It means that the variable has no significant effect for the employee performance in Putra Jaya Sentosa Pekanbaru Company. Meanwhile, the discipline is known that t (5,735)>t table (1,996) and sig (0,000)<0,05. It means that the discipline variables significantly influence of employee performance in Putra Jaya Sentosa Pekanbaru Company. The conclusion is that the discipline variable has a effect of employee performance in Putra Jaya Sentosa Pekanbaru company.Keyword : supervision, discipline, performance, influence.